Early detection, prevention, and mitigation of critical illness outside intensive care settings. Issue 11 (2nd November 2016) - Escobar, Gabriel J.; Dellinger, R. Phillip
Abstract : Patients who deteriorate outside the intensive care unit (ICU) are known to have elevated mortality and morbidity. Rapid response teams (RRTs) were developed to address such deterioration. It has not been possible to establish that RRTs employing manual detection methods have definitively improved hospital outcomes. Because of this, automated early detection systems based on data from modern electronic medical records have been developed. This article attempts to establish a conceptual framework for early detection, prevention, and mitigation of critical illness in hospitalized patients outside the ICU. Taking a step back from the now voluminous clinical and statistical literature on early warning systems, this article focuses on definitional issues (What is early detection? What does it aim to detect, and how?). Particular attention is given to how early detection systems interface with patients who are near the end of life. Also addressed are problems of how one quantifies benefit, which includes consideration of downsides such as potential harms of early detection. Journal of Hospital Medicine 2016;11:S5–S10. © 2016 Society of Hospital Medicine